2009
DOI: 10.1103/physrevlett.102.166802
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and Dephasing in a Two-ElectronC13Nanotube Double Quantum Dot

Abstract: We use charge sensing of Pauli blockade (including spin and isospin) in a two-electron 13 C nanotube double quantum dot to measure relaxation and dephasing times. The relaxation time, T1, first decreases with parallel magnetic field then goes through a minimum in a field of 1.4 T. We attribute both results to the spin-orbit-modified electronic spectrum of carbon nanotubes, which suppresses hyperfine mediated relaxation and enhances relaxation due to soft phonons. The inhomogeneous dephasing time, T * 2 , is co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
234
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(259 citation statements)
references
References 32 publications
(54 reference statements)
20
234
2
3
Order By: Relevance
“…Nevertheless, spin blockade has been observed previously in carbon nanotubes [10,11,13]. In the spin blockade regime, transitions between a (1,1) and (0,2) charge state directly depend on whether the (1,1) state is a singlet or triplet.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, spin blockade has been observed previously in carbon nanotubes [10,11,13]. In the spin blockade regime, transitions between a (1,1) and (0,2) charge state directly depend on whether the (1,1) state is a singlet or triplet.…”
mentioning
confidence: 93%
“…Our measurements thus present a first quantitative analysis of the complex admittance of a double quantum dot. The demonstrated technique also provides the basis for a simple and fast detection scheme for charge and spin state readout in carbon nanotubes -a material with considerable potential for spin-based quantum information processing [8][9][10][11][12][13] -without the need for a separate charge detector [14].…”
mentioning
confidence: 99%
“…18,20 In general, the coupling of the electron spin to its orbital motion is a relativistic effect for electrons moving in external electric fields. Asymmetric confinements in semiconductor QDs ͑extrinsic SO coupling, see Ref.…”
Section: ͑1͒mentioning
confidence: 99%
“…15 Recent experiments have shown that it is indeed possible to confine electrons in single [16][17][18][19] and double QDs ͑DQDs͒ in a CNT by means of electrostatic gates in cleanly grown small band-gap nanotubes. 5,15,20 The present study is motivated by these experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation